The Probiotic Compound VSL#3 Modulates Mucosal, Peripheral, and Systemic Immunity Following Murine Broad-Spectrum Antibiotic Treatment - Ekmekciu, Ira; von Klitzing, Eliane; Fiebiger, Ulrike; Neumann, Christian; Bacher, Petra; Scheffold, Alexander; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Cellular and Infection Microbiology, 2017)
There is compelling evidence linking the commensal intestinal microbiota with host health and, in turn, antibiotic induced perturbations of microbiota composition with distinct pathologies. Despite the attractiveness of probiotic therapy as a tool to beneficially alter the intestinal microbiota, its immunological effects are still incompletely understood. The aim of the present study was to assess the efficacy of the probiotic formulation VSL#3 consisting of eight distinct bacterial species (including Streptococcus thermophilus, Bifidobacterium breve, B. longum, B. infantis, Lactobacillus acidophilus, L. plantarum, L. paracasei, and L. delbrueckii subsp. Bulgaricus) in reversing immunological effects of microbiota depletion as compared to reassociation with a complex murine microbiota. To address this, conventional mice were subjected to broad-spectrum antibiotic therapy for eight weeks and perorally reassociated with either VSL#3 bacteria or a complex murine microbiota. VSL#3 recolonization resulted in restored CD4+ and CD8+ cell numbers in the small and large intestinal lamina propria as well as in B220+ cell numbers in the former, whereas probiotic intervention was not sufficient to reverse the antibiotic induced changes of respective cell populations in the spleen. However, VSL#3 application was as efficient as complex microbiota reassociation to attenuate the frequencies of regulatory T cells, activated dendritic cells and memory/effector T cells in the small intestine, colon, mesenteric lymph nodes and spleen. Whereas broad-spectrum antibiotic treatment resulted in decreased production of cytokines such as IFN-γ, IL-17, IL-22, and IL-10 by CD4+ cells in respective immunological compartments, VSL#3 recolonization was sufficient to completely recover the expression of the anti-inflammatory cytokine IL-10 without affecting pro-inflammatory mediators. In summary, the probiotic compound VSL#3 has an extensive impact on mucosal, peripheral, and systemic innate as well as adaptive immunity, exerting beneficial anti-inflammatory effects in intestinal as well as systemic compartments. Hence, VSL#3 might be considered a therapeutic immunomodulatory tool following antibiotic therapy.